2022
DOI: 10.1007/s40145-021-0555-1
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic, biomorphic cellular Si3N4 ceramics with directional well-aligned nanowhisker arrays based on wood-mimetic architectures

Abstract: Inspired by the transport behavior of water and ions through the aligned channels in trees, we demonstrate a facile, scalable approach for constructing biomorphic cellular Si3N4 ceramic frameworks with well-aligned nanowhisker arrays on the surface of directionally aligned microchannel alignments. Through a facile Y(NO3)3 solution infiltration into wood-derived carbon preforms and subsequent heat treatment, we can faultlessly duplicate the anisotropic wood architectures into free-standing bulk porous Si3N4 cer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Therefore, it can be considered to some extent that the existence of most submicron grains in prepared porous ceramics improves the number of grain boundaries, which is conducive to better J u s t A c c e p t e d stress relief, and hinder the deformation and brittle failure of Y-α-SiAlON porous ceramics to a certain extent [35]. Meanwhile, the mechanical properties can also be improved through the mechanism of crack deflection, crack bridging and grain pullingout effect by successfully introducing Y-α-SiAlON rod-like grains [5,6,36,37]. Table 1 shows the properties of prepared Y-α-SiAlON porous ceramics compared to those of typical high-temperature wave-transmitting materials [16][17][18][38][39][40][41][42].…”
Section: J U S T a C C E P T E Dmentioning
confidence: 99%
“…Therefore, it can be considered to some extent that the existence of most submicron grains in prepared porous ceramics improves the number of grain boundaries, which is conducive to better J u s t A c c e p t e d stress relief, and hinder the deformation and brittle failure of Y-α-SiAlON porous ceramics to a certain extent [35]. Meanwhile, the mechanical properties can also be improved through the mechanism of crack deflection, crack bridging and grain pullingout effect by successfully introducing Y-α-SiAlON rod-like grains [5,6,36,37]. Table 1 shows the properties of prepared Y-α-SiAlON porous ceramics compared to those of typical high-temperature wave-transmitting materials [16][17][18][38][39][40][41][42].…”
Section: J U S T a C C E P T E Dmentioning
confidence: 99%
“…Silicon nitride (Si 3 N 4 ) has high thermal conductivity and excellent mechanical properties, making it one of the ideal fillers for thermal management materials. 21 Ramdani et al reported a thermally conductive composite fabricated via Si 3 N 4 nanoparticles compounded with polybenzoxazine, and the composite thermal conductivity was increased to 5.78 W•m −1 • K −1 by adding 70 wt % of Si 3 N 4 nanoparticles. 22 Considering that one-dimensional (1D) materials have an inherent advantage in building thermally conductive networks, if Si 3 N 4 NWs can be synthesized and further used to prepare thermally conductive composite films by structural design, it will be highly potential to achieve significant enhancement of thermal conductivity at a low filling fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nitride (Si 3 N 4 ) has high thermal conductivity and excellent mechanical properties, making it one of the ideal fillers for thermal management materials . Ramdani et al reported a thermally conductive composite fabricated via Si 3 N 4 nanoparticles compounded with polybenzoxazine, and the composite thermal conductivity was increased to 5.78 W·m –1 ·K –1 by adding 70 wt % of Si 3 N 4 nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nitride (Si 3 N 4 ) ceramics are widely used as structure ceramics for cutting applications due to their good toughness, high strength, low density, high hardness, and good thermal shock resistance. [1][2][3][4][5][6] It has been widely reported that Si 3 N 4 -based ceramic cutting tools can be used for cutting cast iron [7][8][9] and superalloy 10,11 materials.…”
Section: Introductionmentioning
confidence: 99%